Book Review of Is the Bangladesh Paradox Sustainable? The Institutional Diagnostic Project - Abdur Rahman (Universitas Islam Internasional Indonesia (UIII), 2025)
The book Is the Bangladesh Paradox Sustainable? The Institutional Diagnostic Project, edited by Selim Raihan, François Bourguignon, and Umar Salam, delves into the puzzling question of how Bangladesh has managed to achieve sustained economic growth and social progress despite weak formal institutions and governance structures. The volume examines the